2022
DOI: 10.1002/uog.24854
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic artery Doppler at 35–37 weeks' gestation in pregnancies with small or growth‐restricted fetuses

Abstract: Objectives First, to compare the ophthalmic artery peak systolic velocity (PSV) ratio at 35–37 weeks' gestation among women who delivered small‐for‐gestational‐age (SGA) or growth‐restricted (FGR) neonates in the absence of hypertensive disorders, women who developed pre‐eclampsia (PE) or gestational hypertension (GH) and those without SGA, FGR, PE or GH. Second, to examine the association of PSV ratio with placental growth factor (PlGF) and mean arterial pressure (MAP). Third, to assess the associations of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In addition, subgroup analysis revealed that the magnitude of responses was greater in preterm pregnancies although results did not reach statistical significance levels, possibly due to the smaller number of observations. In a previous study in the third trimester, we reported that, in both pregnancies complicated by hypertensive disorders and those delivering a SGA neonate, the PSV ratio was increased, but waveform analysis revealed that the predominant feature in pregnancies complicated by SGA is reduction in PSV1 wave, whereas, in hypertensive disorders, there is an increase in PSV2 wave 13 . This finding demonstrates differences in maternal adaptation during gestation.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In addition, subgroup analysis revealed that the magnitude of responses was greater in preterm pregnancies although results did not reach statistical significance levels, possibly due to the smaller number of observations. In a previous study in the third trimester, we reported that, in both pregnancies complicated by hypertensive disorders and those delivering a SGA neonate, the PSV ratio was increased, but waveform analysis revealed that the predominant feature in pregnancies complicated by SGA is reduction in PSV1 wave, whereas, in hypertensive disorders, there is an increase in PSV2 wave 13 . This finding demonstrates differences in maternal adaptation during gestation.…”
Section: Discussionmentioning
confidence: 70%
“…However, waveform analysis revealed that the predominant feature in pregnancies complicated by SGA was reduction in PSV1, whereas, in hypertensive disorders, there was an increase in PSV2. These findings suggest that the predominant feature of SGA is reduced cardiac output, whereas the main feature of PE is increased peripheral vascular resistance 13 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Pregnancies complicated by delivery of a small-forgestational-age (SGA) neonate, in the absence of hypertensive disorder, share features with pregnancies complicated by PE, including impaired placentation and endothelial dysfunction, and women with these pregnancy complications are at increased risk of long-term development of cardiovascular disease [8][9][10][11][12][13] . Several studies have reported on ophthalmic artery Doppler in SGA pregnancy [14][15][16][17] . A cross-sectional study of 60 pregnancies with SGA at 32-40 weeks' gestation and 60 normal controls reported that the PSV ratio in the SGA group was significantly higher than that in the control group 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A prospective observational study of 499 singleton pregnancies at 11-14 weeks' gestation reported that the PSV ratio in the group of 27 women who delivered a SGA neonate was slightly higher than that in the non-SGA group 15 . We have previously performed two observational studies in women with a singleton pregnancy attending for a routine hospital visit: one in 5214 women at 19-23 weeks' gestation and another in 2287 women at 35-37 weeks 16,17 . In these studies, we found that, compared with unaffected pregnancies, pregnant women who subsequently developed a hypertensive disorder and those delivering a SGA neonate had increased ophthalmic artery PSV ratio and reduced serum placental growth factor (PlGF), but the magnitude of these changes in the SGA group was smaller than that in the PE and gestational hypertension (GH) groups.…”
Section: Introductionmentioning
confidence: 99%